EEG Wavelet Coherence Based Analysis of Neural Connectivity in Action Video Game Players in Attention Inhibition and Short-term Memory-retention Task - Hazarika, Jupitara; Kant, Piyush; Dasgupta, Rajdeep; Laskar, Shahedul H. (Recent Advances in Electrical & Electronic Engineering, 2019)
Background: The involvement in action video gaming alters the cognitive abilities and hence affects the neural functionality. Electroencephalogram (EEG) favorably provides the measure. Wavelet coherence, which is a wavelet transform based feature that provides useful information regarding synchronized activity between two signals. It does not depend on the stationarity of the signal and hence very much relevant for non-stationary EEG application. Methods: We aimed to examine how the task-related synchronization pattern of action video game players (AVGPs) differs from non-AVGPs. EEG data were collected from thirty-five young and healthy male participants while performing an attention inhibition task and a visuospatial short-term memory-retention task. The sub-frequency components, theta, alpha, beta and gamma bands of EEG were extracted using Discrete wavelet transform (DWT). The intra and inter-hemispheric coherence in EEG sub-frequency bands were assessed as a feature for the analysis. Results: Theta, alpha, beta and gamma coherence has shown a significant difference (p<0.05) between AVGPs and non-AVGPs in both the visuo-spatial tasks in intra and inter-hemispheric functionality. More than 90% classification accuracies are achieved with ANFIS algorithm. Results also indicate that frontoparietal connectivity is significantly improved in AVGPs in both the visual sensory tasks considered. Conclusion: These EEG based analysis reports enhanced neural communication with improved attention inhibition and short-term memory retention in AVGPs. Result also established the Wavelet coherence as an effective tool in understanding the neural communication among different brain locations.
Keywords: Attention inhibition